Effect of hyperoxia on the immune status of oxygen divers and endurance athletes. (4th May 2019) - Tillmans, Frauke; Sharghi, Roshanak; Noy, Tatjana; Kähler, Wataru; Klapa, Sebastian; Sartisohn, Simon; Sebens, Susanne; Koch, Andreas
Abstract: Physical activity, particularly that, exerted by endurance athletes, impacts the immune status of the human body. Prolonged duration and high-intensity endurance training lead to increased production of reactive oxygen species (ROS) and thereby to oxidative stress. Military combat swimmers (O2 -divers) are regularly exposed to hyperbaric hyperoxia (HBO) in addition to intensive endurance training intervals. They are, therefore, exposed to extreme levels of oxidative stress. Several studies support that the intensity of oxidative stress essentially determines the effect on immune status. The aim of this study was to comparatively characterise peripheral blood mononuclear cells (PBMCs) of O2 -divers (military combat swimmers), endurance athletes (amateur triathletes), and healthy control volunteers with respect to DNA fragmentation, immune status and signs of inflammation. Furthermore, it was investigated how PBMCs from these groups responded acutely to exposure to HBO. We showed that DNA fragmentation was comparable in PBMCs of all three groups under basal conditions directly after HBO exposure. However, significantly higher DNA fragmentation was observed in O2 -divers 18 hours after HBO, possibly indicating a slower recovery. O2 -divers also exhibited a proinflammatory immune status exemplified by an elevated number of CD4 + CD25 + T cells, elevated expression of proinflammatory cytokine IL-12, and diminished expression of anti-inflammatory TGF-β1 compared to controls. Supported by a decreased basal gene expression and prolonged upregulation of anti-oxidative HO-1, these data suggest that higher oxidative stress levels, as present under intermitted hyperbaric hyperoxia, e.g. through oxygen diving, promote a higher inflammatory immune status than oxidative stress through endurance training alone.